Antidiabetic agents as potential cytotoxic candidates for cancer therapy - Alnaser Raniah I.; Alassaf Fawaz A.; Abed Mohammed N. (Forum of Clinical Oncology)
Hyperglycemia is an overlooked triggering factor for cancer, despite being critical to the survival and growth of cancer cells through a unique process known as the “Warburg effect.” Therefore, blocking glycolysis by using antidiabetic agents is an attractive approach for impeding cancer growth and enhancing their responsiveness to cancer treatments, while leaving healthy cells unaffected. This review aims to explore the potential of antidiabetics as cytotoxic agents for cancer treatment through their role as glucose deprivation candidates and the clinical considerations of using antidiabetics with their risk as carcinogenic in cancer therapy.